Lord Acton for Our Time - Lazarski, Christopher (People for Our Time., 2023)
"The book recreates two fundamental aspects of Acton's teaching, his theory and history of liberty. The evidence both theoretical and historical is to provide us a lesson how to maintain political (civic) liberty and how to avoid mistakes in public life that could lead to great evil"--